T CELL AGING IN RHEUMATOID ARTHRITIS - Maria Oubaid; Bushra tahreem; Toba Samreen; Javeria Parveen; Idress Khan (International Journal of Pharmacy & Integrated Health Sciences)
With the progression of aging, the immune system and the tendency for abnormal immunological changes are common. Individuals over the age of 50 years are susceptible to infectious diseases as well as inflammation and immune-mediated tissue damage. Aging is the main cause of disease pathology and death, continuously enhancing the risk of cardiovascular disease, malignancy, and infectious diseases. One of the important causes is higher susceptibility to autoimmune diseases like rheumatoid arthritis and other immunodeficiency syndromes. Inflammation is common in age-related pathologies. In immune cells, T lymphocytes have an extensive life cycle and show a robust copying force, constructing them sensitive to ageing-associated pathologies. In dysfunctional ageing of T-cells, protection of T-cell function and cells capable of promoting inflammation are abundant. Rheumatoid arthritis is a long-lasting autoimmune disease that mainly affects the joints. Though RA develops at an early age, the frequency of developing RA increases with the increase in age. It is also seen that RA may develop as a result of premature ageing (immunosenescence) of the immune system. In RA, T-cell ageing occurs prematurely, but the mechanism involved and their role in tissue damage is still uncertain. T-cell ageing and its effects on rheumatoid arthritis are discussed here, as well as how T-cells participate in tissue damage, acute and chronic inflammation, and the ageing process. Also review the DNA damage in response to T-cell aging, telomeric ends shortening during RA and immunosenescence, and Tcells in RA.